The Articulation of English Liquids by Annang-English Bilinguals - Utin, Iniobong Dominic (NIU Journal of Humanities, 2024)
This paper investigates the articulation of the English liquids by Annang-English bilinguals. It identifies the liquid sounds and analyses them, taking into consideration the similarities and dissimilarities in both languages. As a result, the theoretical framework employed for the study is provided by the Contrastive Analysis Hypothesis (CAH) propounded by Robert Lado in 1962. Forty subjects drawn from a population of one hundred and twenty (120) Annang-English bilinguals of the Faculty of Arts, Akwa Ibom State University (AKSU), were given a production test of twenty-five (25) items containing the liquid lateral sound and the rhotic. Each subject was required to articulate the words containing the liquid sounds. This was done to ascertain the subject's ability towards articulating these sounds. From the study, it was realised that the subjects had difficulties pronouncing some of the words. Researches in bilingual analysis have shown that the similarities of sounds in both languages facilitate learners’ ability to speaking the language appropriately and differences hinder. This study revealed that although the two liquids are present in the Annang language, the subjects had difficulties articulating the sounds when they were preceded by plosives. These consonant clusters posed a problem to the subjects. It also showed that since the subjects’ speech community uses these liquids in free variation, some of them transferred it to the target language and this affected their pronunciation. Worthy of note is the fact that these problems were not observed at the initial word positions as the subjects were able to appropriately articulate the sounds. In conclusion, if Annang speakers make conscious efforts and are intentional about articulating the right sounds, they will certainly do so. This paper therefore submits that these set of speakers face these problems because of the positions in which these liquids appear in a word. That, the use of liquids in free variation in Annang also hinders them from articulating the words accurately. Keywords: Liquid sounds, Articulation, Free Variation, Bilinguals, Speech community.